Genes transcriptional activity features in different histological subtypes of tongue squamous cell carcinoma - D. S. Kutilin; A. E. Danilova; A. Yu. Maksimov; A. V. Snezhko; M. A. Engibaryan (Успехи молекулярной онкологии)
Introduction. Over the past decade, tongue cancer has maintained a leading position in the overall structure of the incidence of head and neck malignant tumors. Squamous cell carcinoma of the tongue is an aggressive form and has a clinically unpredictable prognosis. Currently, there are several histological subtypes of this disease. And the search for new prognostic factors that could reflect the actual state of tumor progression and give an objective prognosis of disease development is an important research area in molecular oncology. Such factors may be certain transcriptomic characteristics of tumors, which determine the features of pathogenesis in each specific case.Aim. To research genes transcriptional activity features in various histological subtypes of tongue squamous cell carcinoma using bioinformatic and molecular approaches.Materials and methods. The stage of screening bioinformatics analysis was performed using an interactive web server for analyzing data on messenger RNA expression of 9736 tumors and 8587 normal samples from the The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) projects using a standard processing pipeline (GEPIA). The main (validation) stage of the study was performed on 300 patients with locally advanced malignant tumors of the tongue. The quantitative real-time polymerase chain reaction method was used to determine the values of the relative expression of genes identified at the stage of bioinformatic analysis.Results. Bioinformatic analysis identified 1488 genes that increase expression and 589 genes that decrease expression in tongue squamous cell carcinoma. Of these 2077 genes, 23 genetic loci were selected that most strongly alter expression in tumor tissue relative to normal tissue of the tongue. Of these, when validated by polymerase chain reaction, only 14 changed their transcriptional profile in tumor tissue relative to normal: MMP1, MMP11, CA9, PTHLH, MMP9, LAMC2, MMP3, ANXA1, MT-ND6, CRNN, MAL, TGM3, IL1RN and CLU. The analysis of polymerase chain reaction data revealed significant heterogeneity in a number of biological samples studied. Cluster analysis made it possible to divide the total sample of 300 patients into 3 groups differing in gene expression: cluster 1 (n = 90), cluster 2 (n = 101) and cluster 3 (n = 109), corresponding to the basaloid, acantholytic and usual histological subtypes. Thus, the study made it possible to identify a number of molecular markers of tongue squamous cell carcinoma (MMP1, MMP11, CA9, PTHLH, MMP9, LAMC2, MMP3, ANXA1, MT-ND6, CRNN, MAL, TGM3, IL1RN and CLU), as well as to reveal the transcriptional features of various histological subtypes of this disease.